Solid-state NMR investigations of a MgCl2 center dot 4(CH3)(2)CHCH2OH molecular adduct: a peculiar case of reversible equilibrium between two phases - Thushara, K. S.; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Gopinath, Chinnakonda S. (Journal of Physical Chemistry A, 2014)
MgCl2 center dot xROH molecular adducts are extensively employed as a support material for Ziegler-Natta polyolefin catalysis. However, their structural properties are not well understood. Recently, we reported on the preparation of an isobutanol adduct, MgCl2 center dot 4(CH3)(2)CHCH2OH (MgiBuOH) (Dalton Trans. 2012, 41, 11311), which is very sensitive to the preparation conditions, such as the temperature and refluxing time. For the present study, the structural properties of MgiBuOH adducts prepared under different conditions have been investigated thoroughly by solid-state NMR and nonambient XRD. Formation of two phases has been confirmed, and in situ variable temperature solid-state NMR measurements confirm the coexistence of two phases as well as the oscillation from one to another phase. It is expected that such molecular adducts could have a significant role in organic transformation reactions due to an oscillating structural component. An understanding of phase oscillation with the Mg2+ ion as the central metal ion might shed some light toward understanding various biological and structural functions.